Paradigm shift : effective implementation and enforcement of laws to radically accelerate the delivery of quality elementary and further education in South Africa : lessons from China, Finland and Singapore - Sefoka, Isaiah Mmatipa (My University, 2021)
The delivery of substandard education to the leaners in South African schools has become a pressing concern and needs special attention. This is so despite the advent of democracy in 1994, which brought legislative frameworks and other measures promoting access to quality education. This study seeks to highlight the importance of a radical paradigm shift in educational approach, from a single (access) to a dual system (access and delivery) in South Africa. The study examines adequacy of access to education, by evaluating the effectiveness of delivery. The study emphasizes that delivery should be strengthened in order to develop skills and capacity. The study also accentuates the need to strengthen legislative measures and compliance, in order to improve the delivery of quality education to the leaners. The domestic laws such as the Constitution of the Republic of South Africa, Skills Development Act, the South African Schools Act, Further Education and Training Act and the Continuing Education and Training Act, which all cover access and full delivery of quality education, will be examined. It is pertinent to point out that the delivery of quality education and skills development, can improve the employability of leaners and graduates, wherever they find themselves. Consequently, it is fundamentally important to increase interest in strengthening the implementation of the skills development legislation and policies, to drive the necessary change from access to delivery, in order to meet the developmental needs of the country. Lessons are drawn from China, Finland and Singapore, where policies and laws are utilized for the purpose of comparative studies. The rationale for such a comparative analysis is premised on the fact that these countries have very strong educational systems, which promotes the employability of learners, and also enables learners to become self-reliant and entrepreneurs.
Thesis ((LLD.) -- University of Limpopo, 2021
Keywords: Quality education; South African Schools; Employability of learners; Radical paradigm shift; Right to education -- South Africa; Paradigm (Theory of knowledge); Total quality management in education